Traumatic Orbital Emphysema Following Blunt Trauma and Nose Blowing - Ng, Qi Xiong; Lim, Xiao Chien; Chong, Jia Cherng; Hanida, Hanafi; Lim, Lik Thai (Palo Alto, CA : Cureus, Inc., 2023)
Orbital emphysema commonly resolves with no morbidity. However, sight-threatening complications, such as central retinal artery occlusion and ischemic optic neuropathy, may occur, which can result in poor visual outcomes. Plain skull X-ray, which is widely available, is a useful tool in identifying orbital emphysema. We report a case of a 29-year-old gentleman with underlying allergic rhinitis who presented with a painless, progressively increasing periorbital swelling of the right eye, which was aggravated by nose blowing. He had a history of blunt trauma one day prior to the presentation. Visual acuity was unaffected and optic nerve function tests were unremarkable. There was right upper lid swelling with crepitations, right hypoglobus with restricted upward gaze movement, and right conjunctival injection. Intraocular pressure was within normal limits. The posterior segment examination was unremarkable. A plain skull radiograph revealed a “black eyebrow sign” over the right orbit with no obvious orbital wall fracture. Computed tomography of the orbit showed focal indentation over the right lamina papyracea with superior orbito-palpebral emphysema. Systemic antibiotics, steroid nasal spray, and oral antihistamines were initiated with the prohibition of nose blowing. On post-trauma day five, he made an uneventful recovery. High clinical suspicion and thorough clinical examination with the aid of a plain skull radiograph can diagnose orbital emphysema in order for prompt referral to be undertaken to prevent morbidity. Clinicians should consider orbital emphysema as a differential diagnosis for periorbital swelling, especially if there was a preceding trauma.